Blockchain and trustworthy systems : first International Conference, BlockSys 2019, Guangzhou, China, December 7-8, 2019, Proceedings /: first International Conference, BlockSys 2019, Guangzhou, China, December 7-8, 2019, Proceedings. (2020) - Unknown
No abstract available